Wave-CAIPI for highly accelerated 3D imaging - Bilgic, Berkin; Gagoski, Borjan A.; Cauley, Stephen F.; Fan, Audrey P.; Polimeni, Jonathan R.; Grant, P. Ellen; Wald, Lawrence L.; Setsompop, Kawin (Magnetic resonance in medicine, 2015)
Purpose To introduce the wave‐CAIPI (controlled aliasing in parallel imaging) acquisition and reconstruction technique for highly accelerated 3D imaging with negligible g‐factor and artifact penalties. Methods The wave‐CAIPI 3D acquisition involves playing sinusoidal gy and gz gradients during the readout of each kx encoding line while modifying the 3D phase encoding strategy to incur interslice shifts as in 2D‐CAIPI acquisitions. The resulting acquisition spreads the aliasing evenly in all spatial directions, thereby taking full advantage of 3D coil sensitivity distribution. By expressing the voxel spreading effect as a convolution in image space, an efficient reconstruction scheme that does not require data gridding is proposed. Rapid acquisition and high‐quality image reconstruction with wave‐CAIPI is demonstrated for high‐resolution magnitude and phase imaging and quantitative susceptibility mapping. Results Wave‐CAIPI enables full‐brain gradient echo acquisition at 1 mm isotropic voxel size and R = 3 × 3 acceleration with maximum g‐factors of 1.08 at 3T and 1.05 at 7T. Relative to the other advanced Cartesian encoding strategies (2D‐CAIPI and bunched phase encoding) wave‐CAIPI yields up to two‐fold reduction in maximum g‐factor for nine‐fold acceleration at both field strengths. Conclusion Wave‐CAIPI allows highly accelerated 3D acquisitions with low artifact and negligible g‐factor penalties, and may facilitate clinical application of high‐resolution volumetric imaging. Magn Reson Med 73:2152–2162, 2015. © 2014 Wiley Periodicals, Inc.